THE INFLUENCE OF THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON ENVIRONMENTAL POLLUTION MATERIAL AT SMPN 1 SAMADUA ACEH SELATAN - Hasanah, Mauizah; Safriani, Anita; Rosma, Fatemah (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2024)
This research is entitled: